2015
DOI: 10.1016/j.ajo.2014.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Variations of TBK1 in Australian Patients With Primary Open-Angle Glaucoma

Abstract: PURPOSE To investigate the presence of TBK1 copy number variations in a large, well-characterized Australian cohort of patients with glaucoma comprising both normal-tension glaucoma and high-tension glaucoma cases. DESIGN A retrospective cohort study. METHODS DNA samples from patients with normal-tension glaucoma and high-tension glaucoma and unaffected controls were screened for TBK1 copy number variations using real-time quantitative polymerase chain reaction. Samples with additional copies of the TBK1 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 29 publications
5
50
1
Order By: Relevance
“…Ocular disease is no exception, with duplication or triplication of TBK1 in normal tension glaucoma being one example 18,19 , and a complex NHS triplication in the congenital cataract-associated Nance-Horan syndrome being another 20 . TBK1 CNVs associated with glaucoma cover the entire locus, so a mechanistic explanation has not been immediately obvious.…”
Section: Tandem Duplication Of the Crybb1-cryba4 Locusmentioning
confidence: 99%
“…Ocular disease is no exception, with duplication or triplication of TBK1 in normal tension glaucoma being one example 18,19 , and a complex NHS triplication in the congenital cataract-associated Nance-Horan syndrome being another 20 . TBK1 CNVs associated with glaucoma cover the entire locus, so a mechanistic explanation has not been immediately obvious.…”
Section: Tandem Duplication Of the Crybb1-cryba4 Locusmentioning
confidence: 99%
“…Subsequently, screening a larger cohort for this region narrowed down the critical duplication interval to 300 kb which spanned three genes, namely TBK1, XPOT and RASSF3 (Fingert et al 2011;Kawase et al 2012). In addition to the African-American population, the duplication was found in NTG patients of Australian, Caucasian and Japanese ethnicities (Kawase et al 2012;Awadalla et al 2014;Ritch et al 2014). To detect the most likely candidate genes influenced by this duplication, a combination of three factors were considered, namely (i) expression in retinal ganglion cells; (ii) altered expression due to the duplication; and (iii) involvement with known glaucoma genes.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have identified new genetic variations that may contribute to POAG pathogenesis: among them, Caveolin 1 and 2 (CAV1, CAV2) on chromosome 7q31 [7]; tank binding kinase 1 (TBK1) [8,9], transmembrane and coiled-coil domains 1 (TMCO1) on chromosome 1q24 [10,11], S1 RNA binding domain 1 (SRBD1) [12], (CDKN2B-AS1) [11,13].…”
Section: Introductionmentioning
confidence: 99%